2011
DOI: 10.1007/s00464-011-1576-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of hybrid surgical approach of video-assisted minithoracotomy sleeve lobectomy for non-small-cell lung cancer

Abstract: Hybrid VATS sleeve lobectomy is feasible for selected patients with NSCLC in specialized centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 23 publications
(28 reference statements)
0
15
0
Order By: Relevance
“…For a skilled thoracoscopic surgical team, the duration of thoracoscopic bronchial sleeve resection was acceptably longer than that of the thoracoscopic mini-thoracotomy operation. 17 However, when the surgical team becomes more familiar with the procedure of anastomosis techniques, the surgical difficulty is reduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a skilled thoracoscopic surgical team, the duration of thoracoscopic bronchial sleeve resection was acceptably longer than that of the thoracoscopic mini-thoracotomy operation. 17 However, when the surgical team becomes more familiar with the procedure of anastomosis techniques, the surgical difficulty is reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Fiber-optic bronchoscopy was performed prior to discharge to verify proper healing of anastomosis. 17 …”
Section: Intraoperative and Postoperative Managementmentioning
confidence: 99%
“…[11] Most articles report using simple interrupted sutures or Interrupted suture combined with continuous suture, [6,12] but we use a simple continuous sutures. Although the continuous suturing was reported that it may lead to anastomotic leak or anastomotic dehiscence, [6,13,14] our experiences have shown that the continuous suturing can avoid intertwined sutures and shorten the anastomosis time. This suture It is worthwhile to note that our operation method has three features: 1. using only two incisions; 2. the anterior mediastinum fat flap was used to cover the anastomotic stoma; 3. no clamping of bronchus.…”
Section: Discussionmentioning
confidence: 79%
“…Nonsmall cell lung cancer (NSCLC) is the most common lung cancer, whereas surgery remains the preferred treatment for the selected NSCLC cases (2) Complete video-assisted thoracoscopic surgery (VATS) bronchial sleeve lobectomy recognized by the majority of thoracic surgeons worldwide. Many literatures have demonstrated the advantages of VATS techniques, which include small incision, short hospital stay, mild postoperative pain, and small lung damage (3)(4)(5)(6). All these advantages are helpful to facilitate post-operative recovery.…”
Section: Introductionmentioning
confidence: 99%
“…All these advantages are helpful to facilitate post-operative recovery. In recent years, along with improvements in both VATS surgical skills and devices, some doctors have attempted this technique in more challenging procedures such as complete VATS tracheal and bronchial sleeve lobectomy in patients with more complex central-type lung cancer (5,7).…”
Section: Introductionmentioning
confidence: 99%